The Cost of Routine Follow-Up in Total Joint Arthroplasty and the Influence of These Visits on Treatment Plans - Hendricks, Thomas J.; Chong, Alexander C.M.; Cusick, Robert P. (Kansas Journal of Medicine, 2019)
Introduction. Many physicians recommend annual or biennial visitsafter total hip and knee arthroplasty (THA and TKA). This studysought to establish the cost of a post-operative visit to both the healthcare system and patient and identify if these visits altered patientmanagement.Methods. A prospective cohort study was conducted using patientspresenting for follow-up after THA or TKA from April throughDecember 2016. All surgeries were performed by a single orthopaedicsurgeon in Wichita, Kansas. All eligible subjects that met the inclusioncriteria received and completed a questionnaire about the personalcost of the visit and their assessment of their function and outcomeafter total joint arthroplasty. The physician also completed a questionnairethat examined the cost of the visit to the health care systemand whether the clinical or radiographic findings altered patient management.Results. Fifty-six patients participated with an average length of follow-up of 4.5 ± 4.1 years since surgery. The average patient cost was$135.20 ± $190.53 (range, $1.65 - $995.88), and the average visit timefor the patient was 3.9 ± 2.9 hours. Eighty percent of patients reportedno pain during the clinic encounter, and 11% reported loss of function.Eighty-four percent thought the visit was necessary. Physician timefor each visit lasted 12.9 ± 3.7 minutes (range, 10 - 20 minutes). Only9% of patient encounters resulted in an alteration in patient management.This occurred at an average follow-up time of 3.6 ± 1.8 yearsafter the index procedure. The average cost of each visit to the healthcare system at large was $117.31 ± 60.53 (range, $93.90 - $428.28).Conclusions. The findings of this study advise total joint patients andorthopaedic surgeons regarding the cost of routine post-operativeappointments and whether these visits alter patient management.The majority of the routine follow-up visits after THA and TKA didnot result in an alteration in patient management, but added substantialcost to the health care system. Kans J Med 2018;11(3):59-66.